No longer the skunk of the world? Neoliberalism, human rights and contemporary South African foreign policy (1994-2014) - Von Essen, Brendan Craig (My University, 2016)
In the early 1990s South Africa left the Apartheid-era and transformed into a country based on liberal democratic principles such as freedom and human rights. The soon to be inaugurated president, Nelson Mandela, promised that South Africa would base its new foreign policy on these same principles and the pursuit of the international human rights agenda. Initially this seemed to be the case; South Africa signed on to most international human rights conventions and even acted on these principles condemning Nigeria when the ruling regime executed human rights activists. However, once the country gradually began adopting neoliberal ideological positions, first domestically then in its foreign policy, the prominence of human rights in South Africa’s foreign policy began to wane. This is evidenced in South Africa’s actions on international organisations as well as the country’s approach to human rights challenges such as the Zimbabwean crisis in the early 2000s and the furore over planned visit of the Dalai Lama in 2011. Using a hermeneutic approach it is possible to gain an ontological understanding of the process by which this move towards neoliberalism lead to a economisation and commodification of South Africa’s foreign policy between 1994-2014. This in turn undermined the liberal democratic principles which underpinned the country’s international relations leading to a relegation of the human rights agenda to a subsequent by product which can be achieved through greater market liberalisation.
Submitted in accordance with the requirements for the degree of Master of Arts in the field of International Relations, at the University of the Witwatersrand, 2016
Keywords: Human rights--South Africa; Neoliberalism--South Africa; South Africa--Politics and government--1994-; South Africa--Foreign relations--1994-